Bibliometric Analysis of 3D Animation in the Context of Digital Culture: Evolution, Trends and Contributions (2000-2024) - Cantos Luces, Víctor Hugo; Velasco Donoso, Andrea Paola; Gallardo Pérez, Newton Antonio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study presents a bibliometric analysis of 3D animation research in digital culture from 2000 to 2024. It shows a steady growth in scientific output until 2021, driven by technological advances applied to fields such as education, medicine and entertainment. China, the United States and Canada are the main contributors, despite the limited international collaboration, China presents an opportunity to strengthen research in this area. The keyword analysis highlights the increase of topics related to virtual reality, augmented reality and e-learning, which broadens the applications and efficiencies of 3D animation in education and professional fields. The main limitations are the reliance on a single database and the exclusion of documents in other languages, which could underestimate relevant contributions. Therefore, it is recommended to expand the coverage of sources and encourage international collaboration to enhance innovation and academic impact in this field